CDKN1B V109G polymorphism a new prognostic factor in sporadic medullary thyroid carcinoma - Pasquali, Daniela; Circelli, Luisa; Faggiano, Antongiulio; Pancione, Massimo; Renzullo, Andrea; Elisei, Rossella; Romei, Cristina; Accardo, Giacomo; Coppola, Viviana Raffaella; De Palma, Maurizio; Ferolla, Piero; Grimaldi, Franco; et al. (European journal of endocrinology, 2011)
ContextCDKN1B encodes the cyclin-dependent kinase inhibitor p27Kip1 and is mutated in multiple endocrine neoplasia-like syndromes. CDKN1B also harbors single nucleotide polymorphisms; the T/G transversion at nucleotide 326 (the V109G variant) has been reported to be protective in breast, hereditary prostate, and pancreatic tumors. Association of CDNK1B mutations or polymorphisms with sporadic medullary thyroid carcinoma (MTC) has not been investigated yet.Objective and designWe screened germline DNA from 84 patients affected by sporadic MTC and 90 healthy age- and gender-matched controls for CDKN1B mutations or polymorphisms by PCR amplification and sequencing of the amplicons. We also tested all germline and 50 tumor tissue DNA for RET proto-oncogene mutations. Computed tomography, ultrasound scans, and serum calcitonin were carried out before surgery and during the follow-up and associated with CDKN1B polymorphism and disease remission.ResultsThe T/G transversion at nucleotide 326 was the only DNA variation detected. The overall frequency of the T/G and G/G alleles in combination was 46.4%. This variant (V109G) was correlated with post-operative calcitonin levels in the normal range and biochemical remission. Conversely, the wild-type (T/T) allele was associated with post-operative calcitonin levels above normal and a higher risk to develop clinical recurrence and distant metastases. Somatic RET mutations were significantly associated with a more aggressive behavior especially in wild-type allele-bearing patients.ConclusionsCollectively, in sporadic MTC, the CDKN1B V109G polymorphism correlates with a more favorable disease progression than the wild-type allele and might be considered a new promising prognostic marker.